Entrepreneurial Traits and Innovation as Predictors of Business Performance: A Study of Women-Owned Microenterprises in Rural Agam Regency - Feta Maharni; Donard Games; Ratni Prima Lita (Management Institute Faculty of Economics Universitas Andalas, 2025)
This study examines how entrepreneurial traits—risk-taking and need for achievement—influence the performance of rural women-owned microenterprises in Indonesia, with innovation as a mediating variable. Grounded in trait theory and McClelland’s Theory of Needs, it integrates psychological and behavioral perspectives to explore business outcomes in gendered, resource-limited settings. Data were collected from 227 female entrepreneurs in Agam Regency, West Sumatra, via structured questionnaires. PLS-SEM was used to analyze relationships among variables. Findings reveal that both traits positively affect innovation, which in turn enhances entrepreneurial performance. Risk-taking also has a direct impact on performance, while need for achievement operates indirectly through innovation. These results underscore the role of innovation as a key behavioral link between traits and outcomes. Notably, risk-takers may pursue performance through multiple strategies, while high achievers rely on innovation as a path to success. This study contributes to the entrepreneurship literature by contextualizing trait-performance links within rural female entrepreneurship. It offers practical insights for designing targeted programs that strengthen entrepreneurial motivation, innovation capacity, and market communication skills. The findings are relevant for policymakers and development practitioners promoting inclusive economic growth through women’s entrepreneurship.